Immunization practices in athletes - Trabacchi, Valeria; Odone, Anna; Lillo, Lorella; Pasquarella, Cesira; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2015)
Introduction: Immunization practices of athletes is a topic of growing interest in preventive medicine. Several reasons contribute to support such statement including: the demonstrated decrease of the immune response of athletes, the recent increase in vaccine-preventable diseases, the increasing mobility of professional athletes and coaches and sports doctors’ frequent lack of awareness of on the issue of athletes’ immune prophylaxis. Results: This review offers a concise and schematic framework to the immunization practices in athletes, based on the most recent scientific evidences and the vaccine schedules proposed by international organizations and scientific societies including the recent “Life Vaccination Schedule” proposed by four Italian Scientific Societies and Professional Associations. Conclusion: vaccination in athletes, if correctly managed, represents a powerful, costly and long lasting tool for athletes sport teams.